A preliminary study on the mechanism of the Liangzhu culture’s migration across the Yangtze river - Xiao, Jiayi; Shang, Zhiyuan; Zhang, Zixin; Xiao, Shengjun; Jia, Xin (Frontiers in Earth Science, 2023)
The Liangzhu culture (5300–4200 cal BP) was the most famous Neolithic culture of who settled near the lower reaches of the Yangtze River in China. The core and initial distribution area of Liangzhu originated around Taihu Lake, located on the south bank of the Yangtze River delta. Recently, archaeological studies believe that the Jianghuai area and Huanghuai area north of the Yangtze River are also important distribution areas of Liangzhu culture. The route for Liangzhu culture migrating across the Yangtze River is inferred as follows: One would have crossed the Yangtze River from Nanjing-Zhenjiang belt and continued to migrate northward; while the other would have crossed the River near the estuary before moving north along the ancient coastline to the Jianghuai during the late period of Liangzhu, or crossed the Yangtze River from the east of the present Beijing-Hangzhou Grand Canal to Jianghuai and Huanghuai. According to the formation of the Yangtze River delta during the Holocene and the evolution of the estuarine sand bar, it is believed that there were large shoals in the Yangtze River channel in the middle-Holocene. The Liangzhu ancestors around 5000 cal BP had the ability of making canoes over 8 m. Based on the archaeological research of the Neolithic period, the evolution of the Yangtze River channel in the Holocene, the history of ancient Chinese shipbuilding, and the modern examples of crossing the Yangtze River with boat, it can be concluded that the present Changzhou–Jiangyin–Zhangjiagang line should be the main and reasonable route for the Liangzhu culture migrating across the Yangtze River.